How Smart Is “Smart Security”? Exploring Data Subjectivity and Resistance. Final Report - Baur-Ahrens, Andreas; Krüger, Marco; Ammicht Quinn, Regina; Leese, Matthias; Matzner, Tobias

Politische Öffentlichkeit und Big Data - Matzner, Tobias; Heesen, Jessica (Privatheit, Öffentlichkeit und demokratische Willensbildung in Zeiten von Big Data)

Sicherheitsethik in der Anwendung: Ein Praxistest gesellschaftlicher Begleitforschung - Matzner, Tobias; Ammicht Quinn, Regina (Sichere Zeiten?)

Ethik ohne Garantien - Matzner, Tobias (Ethik in den Wissenschaften)

Nanometer Scale Electronic Device Integration Using Side-Wall Deposition and Etch-Back Technology - Hilleringmann, Ulrich; Assion, F.; Vidor, F. F.; Wirth, G. I. (Journal of Machine to Machine Communications)
Keywords: General Medicine

Application of side-wall deposition and etch-back technology for nanometer scale device integration - Hilleringmann, Ulrich; Vidor, F.F.; Assion, F. (Proceedings of the 2nd Pan African International Conference on Science, Computing and Telecommunications (PACT 2014))

Extended event-driven modeling of a ΣΔ-fractional-N PLL including non-ideal effects - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2014 21st IEEE International Conference on Electronics, Circuits and Systems (ICECS))

Fast and accurate event-driven simulation of a mixed-signal system using the example of a PLL - Hangmann, C; Hedayat, C; Hilleringmann, Ulrich (Proc. Int. Conf. Exhib. Integr. Issues Miniatured Syst.)

Religion und Krieg im Medium der Musik: Deutsche Oratorien im Ersten Weltkrieg - Höink, Dominik (Louis Spohr Symposium Braunschweig 2014: „Musik und Politik“. Politische Einflüsse auf Musikerbiografien und kompositorisches Schaffen von 1784 bis heute)

Louis Spohrs Der Fall Babylons und die ,Belsazardramen‘ seit Georg Friedrich Händel - Höink, Dominik (Die Oratorien Louis Spohrs. Kontext – Text – Musik)

Oratorium und Säkularisierung - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

Die Oratorien Louis Spohrs. Kontext – Text – Musik

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

„There’s a better version of you out there.“ Überwachung, Personalisierung und die Sorge um sich im Selbstversuch - Shnayien, Mary (onlinejournal kultur & geschlecht)
In einem Selbstversuch testet die Autorin das Fitnessarmband UP der Firma Jawbone, das auf Basis gesammelter Daten personalisierte Ernährungs-, Schlaf- und Sportempfehlungen ausgeben kann, und zeichnet ihre Erfahrungen mit dem UP-System auf. Dabei wird Personalisierung sowohl als Technologie des Selbst als auch als Überwachungstechnologie bestimmt und die sich an dieser Intersektion ineinander verschränkenden Begehren, Wünsche und Ängste kartographiert.

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Deutungskonflikte um automatisierte Videoüberwachung: Zur sozialen Konstruktion einer Technologie als Instrument der Kriminalitätsbekämpfung - Hälterlein, Jens; Möllers, Norma (Grenzenlose Sicherheit?)

Intelligente Videoüberwachung: eine Handreichung, IZEW Materialien Band 11 - Hälterlein, Jens; Ammicht Quinn, Regina; Koch, Heiner; Held, Cornelius; Matzner, Tobias; Krumm, Julia; Flack, Jaqueline; Markel, Petra; Möllers, Norma; Wittmann, Philipp

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (SPIE Proceedings Vol. 9361: Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Michael Fischer: Religion, Nation, Krieg. Der Lutherchoral EIN FESTE BURG IST UNSER GOTT zwischen Befreiungskriegen und Erstem Weltkrieg, Münster/New York 2014 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Kein feste Burg! Vor 100 Jahren lässt Claude Debussy den Lutherchoral erklingen - Schroeter-Wittke, Harald (Praktische Theologie)

Frömmigkeit und Blasphemie - das geht zu z/weit. - Schroeter-Wittke, Harald (Text-Raum)

Verwirrte Hirten. Talking Horns und St.Ankowski - Schroeter-Wittke, Harald (Praktische Theologie)

Migration und Gender. Medienaneignung in der frühen Bildung in intersektionaler Perspektive - Goetz, Ilka; Günesli, Habib; Marci-Boehncke, Gudrun (Medien + Erziehung)
Dieser Beitrag thematisiert die Perspektive verknüpfter Merkmale in der Wahrnehmung von Kindern im (medialen) Erziehungsprozess durch Eltern und Erzieherinnen. Aufgefallen ist diese Merkmalsverknüpfung – auch „Intersektionalität“ (Collins 1998) – bei der Auswertung eigener empirischer Daten zur Einschätzung von Bildungserfolgen bei vier- und fünfjährigen Jungen und Mädchen mit und ohne Migrationshintergrund (vgl. hierzu Broden/Mecheril 2007) durch ihre Eltern und Erzieherinnen. Diese wird erst dann unterschiedlich, wenn Geschlecht und kultureller Hintergrund gemeinsam als Merkmale berücksichtigt werden. Pädagogisch weist dieses Ergebnis auf Sensibilisierungsbedarf hin, um Bildungsgerechtigkeit kritisch im Blick zu halten.

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Gerechtigkeit als Gegenstand erwägungsorientierten Denkens - Ein Seminarbericht - Jende, Yvonne Kristin; Dear, K.; Garnjost, F.; Höcker, Linus; Matysiak, B.; Täschner, J. (Erwägen - Wissen - Ethik)

Innovative Processing Techniques for the Manufacture of High-Performance Active Elements from Ultra High-Strength Steel Plate - Homberg, Werner; Rostek, Tim

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Fieback, K.; Morbach, A.; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
This study presents the results of an experimental investigation of the influence of latent thermal heat storage elements on the power consumption as well as the temperature distribution of commercial household refrigerators.Two evaporator types and a standard wireand- tube condenser are equipped with copolymer-bound phase change materials (PCM) and the performance is determined under standard conditions. The results show that refrigerating appliances equipped with PCM can be optimized through modifications of the control strategy to achieve different targets: (a) Power consumption can be significantly reduced by increasing the evaporator and decreasing the condenser temperature. (b) Temperature fluctuations in the refrigerator’s fresh-food compartment during the cooling cycle can be reduced from 4 °C to 0.5 °C. (c) The cooling cycle duration can be tripled without compromising the fresh-food compartment conditions. The latter may help to meet the growing demand for balancing power consumption to stabilize the power grid, e.g. if the share of highly fluctuating, sustainable energy supply is large.

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Internal Flow-Turning - An Innovative Technology for the Manufacture of Tailored Tubes - Homberg, Werner; Rostek, Tim; Wiens, Eugen (Key Engineering Materials)
In order to optimise the material utilisation and improve the lightweight design of automotive parts tailored hollow profiles are needed, especially as semi-finished parts for hydroforming. Internal Flow-Turning is an innovative incremental forming technology which enables the manufacture of tubes featuring a varying wall thickness and a constant outer diameter. These characteristics facilitate the material feed at hydroforming processes significantly. In addition, the spinning-related forming technology improves the mechanical material properties, shape and dimensional accuracy, and the surface quality of parts produced.

Vector bundles on plane cubic curves and the classical Yang-Baxter equation - Burban, Igor; Henrich, T. (Journal of the European Math. Society)

Auf der Suche nach digitalen Konzepten - Eickelmann, Birgit (Frankfurter Allgemeine Zeitung Verlagsspezial (V4) zum Tag der Bildung)

Modellierung und Messung medienpädagogischer Kompetenz - Grundlagen und erste Ergebnisse - Herzig, Bardo; Martin, A.; Schaper, N.; Ossenschmidt, D. (Kompetenzerwerb an Hochschulen: Modellierung und Messung. Zur Professionalisierung angehender Lehrerinnen und Lehrer sowie frühpädagogischer Fachkräfte.)

Lernen mit Medien in formalen und informellen Kontexten. - Herzig, Bardo; Martin, A. (Zukunft des Lernens. Neurobiologie und Neue Medien.)

Digitale Medien in der Lehr-Lernforschung. Ergebnisse und Herausforderungen aus interdisziplinärer Sicht - Herzig, Bardo (Medienvielfalt in der Deutschdidaktik. Erkenntnisse und Perspektiven für Theorie, Empirie und Praxis)

Integrative Medienbildung in der Geschichtsdidaktik am Beispiel von TwHistory-Projekten - Aßmann, S.; Herzig, Bardo (Medien machen Geschichte. Neue Anforderungen an den geschichtsdidaktischen Medienbegriff im digitalen Wandel.)

Interaction of high-order solitons with external dispersive waves - Meier, Torsten; Oreshnikov, I.; Driben, R.; Yulin, A.V. (Optics Letters)
The effect of mutual interaction between second-order soliton and dispersive waves (DWs) is investigated. It is predicted analytically and confirmed numerically that DWs (both transmitted and reflected components) become polychromatic after interaction with the soliton. Collision with DWs of considerable intensity can lead to acceleration/deceleration and central frequency shift of the soliton, while still preserving the soliton’s oscillating structure. Two second-order solitons with resonant DWs trapped between them can form an effective solitonic cavity with “flat” or “concave mirrors,” depending on the intensity of the input.

Brücken bauen in der Werkstatt: Die Bedeutung von Forschungswerkstätten in der Bearbeitung des Theorie-Praxis-Verhältnisses in der Lehrer/innenbildung - Freitag, Christine; Thünemann, S. (Brücken bauen – Praxisforschung zu Übergängen im Bildungssystem)

Gewalt und Zuchtmittel in der Schulgeschichte - Freitag, Christine (Handbuch Aggression, Gewalt und Kriminalität bei Kindern und Jugendlichen)

Anaerobic Microbial Transformation of Halogenated Aromatics and Fate Prediction Using Electron Density Modeling - Cooper, M.; Wagner, A.; Wondrousch, D.; Sonntag, F.; Sonnabend, A.; Brehm, Martin; Schüürmann, G.; Adrian, L. (Environ. Sci. Technol.)

Triphilic Ionic-Liquid Mixtures: Fluorinated and Non-Fluorinated Aprotic Ionic-Liquid Mixtures - Hollóczki, O.; Macchiagodena, M.; Weber, H.; Thomas, M.; Brehm, Martin; Stark, A.; Russina, O.; Triolo, A.; Kirchner, B. (ChemPhysChem)